The subaltern Ulysses - Duffy, Enda (University of Minnesota Press, 1994)
Reveals that James Joyce's Ulysses can be seen as a guerrilla text written to resist colonialism.
Keywords: Joyce, James, -- 1882-1941. -- Ulysses.; Joyce, James, -- 1882-1941 -- Political and social views.; Joyce, James, -- 1882-1941 -- Ulysses.; Joyce, James, -- 1882-1941 -- Pensée politique et sociale.; Joyce, James, -- 1882-1941; Ulysses (Joyce, James); Politics and literature -- Ireland -- History -- 20th century.; Colonies in literature.; Ireland -- Politics and government -- 20th century.; Ireland -- In literature.; Politique et littérature -- Irlande -- Histoire -- 20e siècle.; Colonies dans la littérature.; Irlande -- Politique et gouvernement -- 20e siècle.; Irlande dans la littérature.; Irlande -- Dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Colonies in literature; Literature; Political and social views; Politics and government; Politics and literature; Ireland; Ulysses (Joyce); Postkolonialisme.; 1900-1999; History